2006
DOI: 10.1016/j.cell.2006.10.031
|View full text |Cite
|
Sign up to set email alerts
|

A Neuronal Identity Code for the Odorant Receptor-Specific and Activity-Dependent Axon Sorting

Abstract: In the mouse, olfactory sensory neurons (OSNs) expressing the same odorant receptor (OR) converge their axons to a specific set of glomeruli in the olfactory bulb. To study how OR-instructed axonal fasciculation is controlled, we searched for genes whose expression profiles are correlated with the expressed ORs. Using the transgenic mouse in which the majority of OSNs express a particular OR, we identified such genes coding for the homophilic adhesive molecules Kirrel2/Kirrel3 and repulsive molecules ephrin-A5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
450
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(474 citation statements)
references
References 48 publications
20
450
1
3
Order By: Relevance
“…Recently, other Neph family members, Neph2 and Neph3, have been reported to be involved in odorant receptor-specific segregation of axon termini, by their homophilic interaction (50). Phosphorylation of Neph2 or Neph3 is not well characterized, but the binding motif for Grb2 is not conserved in these two proteins, suggesting that negative feedback control for ERK by binding to Grb2 may be unique to Neph1.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, other Neph family members, Neph2 and Neph3, have been reported to be involved in odorant receptor-specific segregation of axon termini, by their homophilic interaction (50). Phosphorylation of Neph2 or Neph3 is not well characterized, but the binding motif for Grb2 is not conserved in these two proteins, suggesting that negative feedback control for ERK by binding to Grb2 may be unique to Neph1.…”
Section: Discussionmentioning
confidence: 99%
“…Axons are first routed to their approximate target via odorant-independent events, and targeting is then refined in an activity-dependent manner. This refinement is thought to occur by regulating the identity and abundance of axon guidance and cell adhesion molecules, including Kirrel 2/3 and BIG2 (22,23), via canonical OR-mediated signaling. Our data are consistent with the above model of olfactory axon targeting.…”
Section: Discussionmentioning
confidence: 99%
“…The observed defects in cilia and transduction component distribution suggest that Bbs8-null OSNs may exhibit a perturbed location of transduction or spontaneous signaling activity. Previous studies indicated a role for OR levels and associated transduction activity in appropriate axon targeting to the OB by regulation of axon guidance molecule levels (22,23). Bicistronic transcription of the M72 OR mRNA with the tau:lacZ reporter (M72 TL ) allows for visualization of soma and axonal projections for OSNs expressing the same OR.…”
Section: Loss Of Bbs8 Reduces Olfactory Sensitivity and Causes Structmentioning
confidence: 99%
“…spécifique et innée, pouvant être à l'origine d'une susceptibilité aux infections bactériennes [9][10][11] et du déclenchement de mécanismes inflammatoires intestinaux, dépendants ou non de la présence de lymphocytes T ou B [7,8]. Ainsi, si l'on considère l'allèle rare du polymorphisme de l'IL-23R codant pour l'arginine en positon 381 (Arg381) dans la partie très conservée intracytoplasmique du récepteur, cette modification pourrait augmenter la fonction de l'IL-23 et confé-rer à la muqueuse iléale une meilleure résistance aux agressions bactériennes, protégeant contre la survenue de la MC.…”
unclassified
“…Les mécanismes intervenant dans l'établissement d'une « connectique » bien plus précise lorsque les axones ont atteint approximativement leur cible commencent à être élucidés. La même équipe vient en effet de démontrer que selon l'identité du récepteur olfactif présent dans un neurone, certaines molécules d'adhérence cellulaire et de répulsion sont spécifiquement exprimées et régulées d'une manière dépendante de l'activité [9]. Jusqu'à maintenant, selon l'opinion générale, l'activité sensorielle n'est pas requise pour la mise en place des connexions appropriées dans le bulbe et ces nouveaux résultats posent de nou- Pour analyser les informations visuelles, auditives, gustatives ou tactiles, les systèmes sensoriels correspondants ont développé un nombre limité de récepteurs et les ont répartis sur la surface de l'organe sensoriel de façon à ce qu'une partie du codage de l'information afférente renseigne sur la localisation précise des récepteurs activés par le stimulus.…”
unclassified